KARAKTERISTIK PENGERINGAN KELAPA PARUT MENGGUNAKAN ALAT PENGERING SILINDER TIPE RAK - Hary Kurniawan; Abdul Muiz; Muhamad Ikhsan Febriyanto Mbele; Rizka Okta Dini; Zulhan Widya Baskara; Zulhan Widya Baskara (AGROINTEK, 2020)
Desiccated coconut is one of the diversification of coconut products which is cut into pieces or grated into small pieces and dried, white, sweet taste and distinctive odor. The purpose of this study was to determine the drying characteristics of desiccated coconut using a cylindrical dryer. Eight trays, each containing 350 grams of grated coconut, were arranged on a tray and measured the air temperature in the drying chamber, the temperature of the material, as well as the moisture content of the material during drying both on the top rack, middle rack and bottom rack. The results showed that the air temperature in the drying chamber and the temperature of the material were significant, and moisture content during drying of materials both on the top rack, middle rack and bottom are relatively significant. The constant rate of drying of grated coconut on the upper rack, middle rack and lower rack is 0.1306 - 1338 minutes-1. The predicted value of grated coconut water content shows that it is almost close to the observed water content value, which is marked by a coefficient of determination that is close to 1.